A phytoplasma survey reveals the presence of 'Candidatus Phytoplasma fragariae' in Ulmus spp. and Acer pseudoplatanus in Belgium. Issue 5 (22nd September 2020) - De Jonghe, Kris; Goedefroit, Thomas; Deeren, Anne‐Marie; Fauche, Frédéric; Steyer, Stéphan
Abstract: A Belgium‐wide survey to determine the presence of ' Candidatus Phytoplasma ulmi' elm trees was performed on nearly 600 elm trees. The randomly sampled elms were screened for the presence of phytoplasmas using a standard generic nested PCR method. In five symptomless elm trees, phytoplasmas were detected. Multiple gene sequence analysis (16S rRNA, tuf, rplV‐rpsC‐rplP), virtual RFLP of the 16S rRNA gene fragment and phylogenetic analysis showed that the phytoplasma strains detected in all five elm trees could be classified into the 16SrXII‐E subgroup (' Candidatus Phytoplasma fragariae'‐related phytoplasma). In addition, a maple tree ( Acer pseudoplatanus ) located in close proximity to one of these elm trees was also determined to be infected with ' Ca . P. fragariae'. Ulmus and Acer are new host plant genera for this phytoplasma. Further studies are needed to elucidate the epidemiological impact of these findings.